Teacher preparation for emergent bilingual students: Implications of evidence for policy - Francesca Lopez; Lucrecia Santibanez (Arizona State University, 2018)
Failure to adequately prepare teachers of emergent bilingual (EB) students could have devastating consequences for student achievement, EB reclassification, and eventually, high school and college completion. To enhance the policy discourse, we explore how teacher certification requirements relate to both EB student achievement and teacher self-efficacy in three states with similar EB student populations but disparate policies on ways to meet EBs' needs: Arizona, California, and Texas. To do this we ask: (1) How well do states prepare their teachers to meet the needs of EBs? (2) What knowledge specific to meeting EBs' needs do states require their teachers to demonstrate? (3) How are these requirements related to teacher perceptions of their preparedness to effectively teach EBs? We find that there are marked differences across the three states in terms of how well they prepare EBs, and these patterns can be discerned from their teacher preparation requirements. Although teachers' self-efficacy does not appear to be related to teacher training in the first three years of teaching, there is an advantage to more rigorous training over time. Implications for policy are discussed.